Management of sleeve gastrectomy leakage: case report - Almeida, Ana C.; Guimarães, Andreia; Amaral, Maria J.; Andrade, Rita; Bernardes, António (International Surgery Journal, 2021)
Treatment of postoperative gastric fistula complicated by local and systemic infection is difficult and controversial, particularly when treating obese patients with multiple prior surgical procedures. A 41-year-old male patient was transferred to our hospital to be admitted in the Intensive Care Unit with respiratory failure and postoperative sepsis, after being submitted to bariatric surgery. He had been through four subsequent surgical procedures: 1- a laparoscopic sleeve gastrectomy; 2- an exploratory laparotomy for unproven suspected subphrenic abscess; 3- a laparotomy with splenectomy and peritoneal drainage for splenic and peri-splenic abscess; 4-celiotomy and lavage for purulent peritonitis. Due to persistent clinical and analytical deterioration, and suspicion of left subphrenic abscess and digestive fistula, we proceeded to: identification and drainage of the abscess, adhesiolysis, identification of fistula orifice at the cardiac incisure (methylene blue and perioperative endoscopy), placement of a Pezzer tube for directed and controlled fistulization, Shirley’s drain in the subphrenic space for continuous lavage, jejunostomy for enteral nutrition. Under clinical and imaging control (esophageal transit, fistulography and computed tomography with water-soluble contrasts) he was started on a water diet 2 months after and the Shirley’s drain was later removed. Patient was discharged two and a half months after the intervention, maintaing the Pezzer tube and under enteral nutrition by jejunostomy. Oral feeding started in the 3rd postoperative month and jejunostomy and Pezzer probes were removed. Patient was asymptomatic at seven-month postoperative outpatient appointment.